Beyond the Nest : Navigating Strategic Challenges in Industry Platform Management - Abed Alghani, Khaled (Vaasan yliopisto, 2025)
The proliferation of industry platforms has captured significant attention from both industry professionals and academic researchers. Practitioners have embraced industry platforms to harness the economic benefits of network externalities, while scholars have focused on examining this blockbuster business model to understand the intricate dynamics of managing industry platforms. Not all firms that have embraced industry platforms have succeeded, and studies examining the challenges faced by platform owners have not yet provided a comprehensive understanding of these challenges or the strategies required to successfully manage industry platforms. This might stem from the fact that the majority of academic discourse has extensively focused on the chicken-and-egg dilemma, or deciding whom to attract first, ultimately portraying it as the primary strategic challenge in managing industry platforms. Consequently, this dissertation aims to uncover the strategic challenges of managing industry platforms, as well as the strategies employed to overcome them. Considering the objectives of this dissertation on one hand, and the dynamic and complex nature of industry platforms on the other, a structurationist approach is adopted to achieve its goals. Initially, this dissertation maps the landscape of the literature by exploring the diverse perspectives (clusters) that examine industry platforms. With a grasp of the field’s structure and an aim to systematically identify the challenges, this dissertation outlines the processes central to managing industry platforms, namely creation, integration, orchestration, navigation, and evolution, and highlights the chicken-and-egg dilemma as falling in a gray area between the creation and integration processes. Drawing on empirical evidence, and supported by conceptual analysis, this dissertation examines the creation and integration processes, arguing that the chicken-and-egg dilemma is primarily associated with the integration process rather than the creation process. Despite their interdependence, the creation process involves strategic challenges that precede the chicken-and-egg dilemma and are at least as challenging, if not more, yet remain largely overlooked in the literature. Additionally, this dissertation outlines key strategies that platform owners can adopt to effectively address the challenges associated with the creation and integration processes. Therefore, this dissertation contributes to the ongoing strategic management discussions on industry platforms, particularly those addressing platform owners’ management of industry platforms.

Alustojen (industry platform) yleistyminen on herättänyt huomiota sekä teollisuuden ammattilaisten että akateemisten tutkijoiden keskuudessa. Yritykset ovat pyrkineet kehittämään alustoja taloudellisten verkostovaikutusten hyödyn-tämiseksi. Samanaikaisesti tutkijat ovat suunnanneet huomionsa tämän liiketoimintamallin tutkimiseen ymmärtääkseen sen monimutkaisia dynamiikkoja. Kaikki alustoja perustaneet yritykset eivät kuitenkaan ole onnistuneet hankkeissaan, ja tutkimukset, jotka ovat tarkastelleet alustanomistajien kohtaamia strategisia haasteita, eivät ole vielä tarjonneet kattavaa ymmärrystä näistä kysymyksistä tai strategioista, jotka ovat tarpeen alustan menestyksekkäälle perustamiselle. Tämä saattaa johtua siitä, että suurin osa keskusteluista on keskittynyt niin kutsuttuun muna-kana-dilemmaan, eli siihen, mitä toimijoita pitäisi houkutella alustalle ensin, esittäen muna-kana -dilemman pääasiallisena strategisena haasteena alustaa luotaessa. Tämä väitöskirja pyrkii paljastamaan alustojen hallinnan strategiset haasteet, etenkin alustan luomisprosessin aikana, ja strategiat näiden haasteiden voittamiseksi. Ottaen huomioon tämän väitöskirjan tavoitteet ja alustojen dynaamisen, moni-mutkaisen luonteen, tutkimuksessa hyödynnetään seuraavanlaista lähestymistapaa sille asetettujen tavoitteiden saavuttamiseksi. Aluksi väitöskirja kartoittaa teollisuusalustojen kirjallisuutta tunnistamalla klusterit, jotka tutkivat alustailmiötä erilaisista näkökulmista. Kirjallisuuden rakenteen ymmärtämisen myötä tunnistetaan myös keskeiset prosessit teollisuusalustojen hallinnassa: luominen, integrointi, orkestrointi, navigointi ja evoluutio, joista muna-kana -dilemma sijoittuu harmaalle alueelle luomisen ja integroinnin prosessien välille. Empiirisen aineiston ja käsitteellisen analyysin avulla tämä väitöskirja väittää, että muna-kana -dilemma liittyy integrointiprosessiin, ei luomisprosessiin. Huolimatta niiden keskinäisestä riippuvuudesta, luomisprosessiin sisältyy strategisia haasteita, jotka edeltävät muna-kana -dilemmaa. Nämä haasteet ovat yhtä haastavia tai jopa haastavampia kuin muna-kana -dilemma, mutta ne on suurelta osin sivuutettu kirjallisuudessa. Lisäksi väitöskirja hahmottelee keskeisiä strategioita, joita alustan omistajat voivat sisällyttää käsitelläkseen tehokkaasti sekä luomisen että integroinnin prosessien haasteita. Näin ollen tämä väitöskirja edistää jatkuvia strategisen johtamisen keskusteluja alustoista, etenkin niitä keskusteluja, jotka käsittelevät luomisen ja integroinnin prosesseja.
Keywords: leadership (activity); enterprises; organisations (systems); development (active); strategic leadership; strategic planning; strategies; business operations; fi=Strateginen johtaminen|en=Strategic Management|